Sleep-time blood pressure: Unique sensitive prognostic marker of vascular risk and therapeutic target for prevention. (June 2017) - Hermida, Ramón C.; Ayala, Diana E.; Smolensky, Michael H.; Fernández, José R.; Mojón, Artemio; Portaluppi, Francesco
Summary: Correlation between blood pressure (BP) and target organ damage, vascular risk, and long-term patient prognosis is stronger for measurements derived from around-the-clock ambulatory BP monitoring (ABPM) than in-clinic daytime ones. Numerous studies consistently substantiate the asleep BP mean is both an independent and much better predictor of cardiovascular disease (CVD) risk than either the awake or 24 h means. Elevated sleep-time BP, i.e., sleep-time hypertension, which can only be diagnosed by around-the-clock ABPM, is much more common than suspected, not only in patients with sleep disorders, but, among others, in those who are elderly or have type 2 diabetes, chronic kidney disease, or resistant hypertension. Hence, medical guidelines increasingly recommend ABPM to make the accurate differential diagnosis of hypertension versus normotension and recognize the marked clinical importance of adequate management of sleep-time BP. The ingestion time, according to circadian rhythms, of hypertension medications of six different classes and their combinations significantly impacts their beneficial, particularly on sleep-time BP control, and/or adverse effects. The MAPEC (monitorización ambulatoria para predicción de eventos cardiovasculares (i.e., ambulatory blood pressure monitoring for prediction of cardiovascular events)) study was the first prospective randomized treatment-time investigation designed to test the worthiness of bedtime chronotherapy with ≥1 conventional hypertension medications to specifically target attenuation of asleep BP. This 5.6 y median follow-up outcomes trial found the bedtime chronotherapy strategy most advantageous, resulting in the differential reduction of total CVD events by 61% and decrease of major CVD events – CVD death, myocardial infarction, and ischemic and hemorrhagic stroke – by 67%. The MAPEC study plus other earlier conducted less refined trials document the asleep BP mean is the most significant prognostic marker of CVD morbidity and mortality. It further substantiates attenuation of the asleep BP mean by a bedtime hypertension treatment strategy entailing the entire daily dose of ≥1 hypertension medications significantly reduces CVD risk, both in the general hypertension population and in more vulnerable patients, i.e., those diagnosed with chronic kidney disease, diabetes, and resistant hypertension.